Wilms' tumor and benign renal tumor combined with hypospadias and incomplete orchiocatabasis appearing simultaneously in a 10 months old boy - Li, Chun; Li, Wei-Song (Urology Journal, 2020)
We herein report a case of left renal Wilms’ tumor and right renal hamartoma combined with hypospadias and incomplete orchiocatabasis in a 10-month-old boy. In the literature to date, no case has been reported. The preoperative abdominal computerized tomography (CT) scan was suggestive of bilateral nephroblastomas, and clinical diagnosis was bilateral renal tumors with external genitals malformation, a syndrome? Finally, this case was used by B-ultrasonic guided percutaneous biopsy to help determine the nature of bilateral renal tumors. Afterwards, the boy underwent preoperative chemotherapy, surgery ( a left radical nephrectomy and right wedge excision of the renal tumor) and postoperative chemotherapy. After 3 years of follow-up, there was no evidence of tumor recurrence, the renal function was normal, and the boy’s height, weight and intelligence were also within normal range. Owing to no similar cases as a reference, we discussed the preoperative imaging diagnosis, final etiological diagnosis and appropriate treatment of this disease. Long-term follow-up with a sufficient number of cases may be needed to optimize methods of diagnosis and define optimal treatment options for patients with this extremely rare disease.